The Cathars: dualist heretics in Languedoc in the High Middle Ages - Barber, Malcolm (The medieval world, 2000)
Klappentext: The Cathars were dualist heretics who, in the twelfth and early thirteenth centuries, presented more coherent doctrinal opposition to the Catholic church than any contemporary movement. They were present in most areas of Latin Christendom, but they were particularly strong in southern France and northern Italy, where they drew adherents from all social classes. This new book traces the origins and spread of dualist ideas, assesses their attraction for contemporaries, and describes the reaction of the ecclesiastical and lay authorities in the form of preaching campaigns, intellectual refutation, crusade, and inquisitorial investigations. A fascinating account of the development of radical religious belief and the means used to suppress it, this book raises many important issues which transcend the specifics of time and place, including the nature of evil, the ethics of warfare, and the use made of history by later generations. Richly illustrated, this book will have a wide appeal for all those interested in medieval perceptions of the world, the Crusades and the Inquisition. Malcolm Barber is Professor of History at the University of Reading. He is the author of The Two Cities:Medieval Europe, 1050-1320 (1992), and two books on the Templars, The Trial of the Templars (1978) and The New Knighthood (1994).